A minimally invasive approach to induce myocardial infarction in mice without thoracotomy. Issue 11 (14th September 2018) - Sun, Quan; Wang, Kang‐Kai; Pan, Miao; Zhou, Ji‐Peng; Qiu, Xue‐Ting; Wang, Zhen‐Yu; Yang, Zhen; Chen, Yan; Shen, Hong; Gu, Qi‐Lin; Fang, Long‐Hou; Zhang, Guo‐Gang; et al.
Abstract: Acute myocardial infarction (MI) is a leading cause of morbidity and mortality in the world. Traditional method to induce MI by left coronary artery (LCA) ligation is typically performed by an invasive approach that requires ventilation and thoracotomy, causing serious injuries in animals undergoing this surgery. We attempted to develop a minimally invasive method (MIM) to induce MI in mice. Under the guide of ultrasound, LCA ligation was performed in mice without ventilation and chest‐opening. Compared to sham mice, MIM induced MI in mice as determined by triphenyltetrazolium chloride staining and Masson staining. Mice with MIM surgery revealed the reductions of LVEF, LVFS, E/A and ascending aorta (AAO) blood flow, and the elevations of S‐T segment and serum cTn‐I levels at 24 post‐operative hours. The effects of MI induced by MIM were comparable to the effects of MI produced by traditional method in mice. Importantly, MIM increased the survival rates and caused less inflammation after the surgery of LCA ligation, compared to the surgery of traditional method. Further, MIM induced angiogenesis and apoptosis in ischaemic hearts from mice at postoperative 28 days as similarly as traditional method did. Finally, the MIM model was able to develop into the myocardial ischaemia/reperfusion model by using a balloon catheter with minor modifications. The MI model is able to be efficiently induced by a minimally invasive approach in mice without ventilation and chest‐opening. This new model is potentially to be used in studying ischaemia‐related heart diseases.